Introduction to tourism and hospitality industry - Andrews, Sudhir (New Dellhi, 2007)
The book focuses on the new trends and developments in the hospitality industry while giving it a perspective with the evolution of travel, tourism, and distribution from the early times.
Keywords: Hospitality industry- Management; Tourism management